PENGEMBANGAN ASUHAN KOMUNITAS PADA LANSIA DENGAN PENDEKATAN KOMPLEMENTER PENGGUNAAN REBUSAN DAUN ALPUKAT DALAM PENURUNAN HIPERTENSI - Meda Yuliani; Iceu Mulyati; Yuni Mauliany; Susilawati Susilawati; Nabila Berliana; Amirah Salwa; Lika Nurfiati (JURNAL KESEHATAN INDRA HUSADA, 2022)
Chronic high blood pressure (hypertension) is a prevalent ailment among the elderly. One of the most prevalent causes of mortality is hypertension.Hypertension is one of the difficulties in the elderly since it produces and is a factor in heart failure and coronary heart disease. Both pharmacological and non-pharmacological methods may be used to treat hypertension. Non-pharmacological avocado leaf decoction has been used in research for years and is readily available. In this research, an avocado leaf decoction is used as a supplemental treatment for the elderly with hypertension. To begin, the process of evaluation, examination, and provision of complementary care treatments is used in conjunction with a case study approach with a descriptive design. There was a significant drop in blood pressure in the elderly with hypertension following the avocado leaf decoction intervention compared to the pre intervention average of 171/101mmHg and the postintervention average of 148/89mmHg. The mean decrease was 23/12 mmHg. Avocado leaf decoction helps lower blood pressure in older patients with hypertension This avocado leaf decoction is anticipated to be used as an antihypertensive and as self-medication to decrease blood pressure through future investigations on this avocado leaf decoction in the medical field. Keywords: Hypertension, Elderly, Avocado leaf decoction